The exceptional hydrological disaster of April-May 2024 in southern Brazil - Walter Collischonn; Fernando Mainardi Fan; Iporã Possantti; Fernando Dornelles; Rodrigo Paiva; Matheus Sampaio Medeiros; Gean Paulo Michel; Fernando Jorge Corrêa Magalhães Filho; Sofia Royer Moraes; Francisco Fernando Noronha Marcuzzo; Rossano Dalla Lana Michel; Tamara Leitzke Caldeira Beskow; et al. (Revista Brasileira de Recursos Hídricos)
ABSTRACT We present an overview of the unprecedent hydrological event that occurred in Rio Grande do Sul state in late April and early May 2024, causing floods and landslides in a scale that was not seen before in Brazil. The rainfall that caused the disaster is incomparable to any recent event in Brazil at large spatial and temporal scale. The intense and long-lasting precipitation led to record floods from small rivers with drainage areas below 1000 km2 to the Patos Lagoon, which drains more than 180,000 km2. The rainfall also led to landslides that rank first in Brazil in terms of spatial scale and number of occurrences. Mountain rivers experienced flash floods with extreme water levels, while in the lowlands the large rivers and the Patos Lagoon experienced long duration flooding, with stage remaining high for about 30 days. The flood event is probably ranked first in terms of displaced people and damage to property and infrastructure in Brazil. Almost 200 fatalities occurred due to the disaster and protection structure failures. The April-May hydrological event show a glimpse of what can be expected along the coming decades due to climate change in a region that covers South Brazil, and parts of the neighboring countries.